2010
DOI: 10.1038/ismej.2010.12
|View full text |Cite
|
Sign up to set email alerts
|

Silica deposition and phenotypic changes to Thermus thermophilus cultivated in the presence of supersaturated silicia

Abstract: Thermus thermophilus cells formed siliceous deposits in the presence of supersaturated silicic acid (600 p.p.m SiO 2 ). The supersaturated silicic acid promoted interaction between cells and the inside walls of glass culture bottles, leading to the development of cell aggregates or biofilms. Electron probe microanalysis showed that within the aggregates most of the cell surfaces were covered with silica. Under these conditions, there was remarkable production of silica-induced protein (Sip), a solute-binding c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…In a silicifying environment, cells can change their metabolisms (through protein expression, modification of the cell wall properties, production of EPS), thus implementing a survival strategy that limits the detrimental effects of the fossilization (i.e., blocking of exchange with the surrounding environment, damage to cell structure and eventually death) Lalonde et al 2005;Saw et al 2008;Iwai et al 2010). In particular, while encapsulating a close relative to Geobacillus SP7A (the thermophilic Anoxybacillus flavithermus), Saw et al (2008) noticed the ability of this species to survive silicification and to adapt its metabolism accordingly.…”
Section: Preservation Of the Cells And Of Their Structural Integritymentioning
confidence: 99%
See 1 more Smart Citation
“…In a silicifying environment, cells can change their metabolisms (through protein expression, modification of the cell wall properties, production of EPS), thus implementing a survival strategy that limits the detrimental effects of the fossilization (i.e., blocking of exchange with the surrounding environment, damage to cell structure and eventually death) Lalonde et al 2005;Saw et al 2008;Iwai et al 2010). In particular, while encapsulating a close relative to Geobacillus SP7A (the thermophilic Anoxybacillus flavithermus), Saw et al (2008) noticed the ability of this species to survive silicification and to adapt its metabolism accordingly.…”
Section: Preservation Of the Cells And Of Their Structural Integritymentioning
confidence: 99%
“…Recently, microbial response to silicification has been investigated and it has been shown that microorganisms can implement various strategies to deal with a silica saturated environment (Iwai et al 2010;Konhauser et al 2008;Lalonde et al 2005;Saw et al 2008). The main effect of these strategies is that mineralization is limited to the outer part of the cell wall (Phoenix et al 2000), thus allowing the cell to continue to live.…”
Section: Introductionmentioning
confidence: 99%
“…cDNA was generated and used for quantitative real-time PCR {SYBR Green qPCR Kits [(2×) without ROX]} (Fisher Scientific GmbH, Schwerte, Germany). The amplification conditions were 300 s at 98°C followed by 40 cycles at 98°C for 30 s, annealing at 67°C for 15 s and an elongation at 72°C for 15 s. To exclude changes in expression, two recently published house-keeping genes, encoding glutamate-dehydrogenase B (TTC1211) and gyrase subunit B (TTC1622), were used (Cava et al, 2008;Iwai et al, 2010). To determine the changes in mRNA expression levels, the comparative threshold cycle (Ct) method (2 −ΔΔCt ) was used (Livak and Schmittgen, 2001;Schmittgen and Livak, 2008).…”
Section: Qrt-pcrmentioning
confidence: 99%
“…Primer design and the PCR conditions were the same as described previously (19). The primers used are listed in Table S1 in the supplemental material.…”
Section: Methodsmentioning
confidence: 99%
“…After cultivation for an additional 1 h at 70°C, the cultures were collected, treated with RNAprotect Bacteria reagent (Qiagen, Hilden, Germany), and stored at Ϫ80°C until needed. Total RNA extraction and purification were carried out as described previously (19).…”
Section: Methodsmentioning
confidence: 99%